Training practices of Japanese elite team and combat sport athletes during the COVID-19 pandemic: an interview study with support staff - Yamashita, D.; Yamazaki, K.; Yamagishi, T.; Tsubokura, H.; Washif, J. A.; Mujika, I. (Frontiers in Sports and Active Living, 2025)
Background: The coronavirus disease 2019 (COVID-19) pandemic had a profound impact on the world of sports, particularly elite athletes. This study aimed to investigate how elite athletes adapted their training during the pandemic through semi-structured interviews with performance support staff from national (NT) and professional (PT) teams.